Empoderamento e recursos para a participação em conselhos gestores Empowerment and resources for participation in management councils - Águeda L. P. Wendhausen; Tatiane Muniz Barbosa; Maria Clara de Borba (Universidade de São Paulo, 2006)
A criação de conselhos gestores a partir de 1988 suscitou diversas experiências participativas, embora ainda predominem práticas autoritárias que inviabilizam a participação e o empoderamento. O objetivo deste estudo foi mapear recursos para o empoderamento/participação, em quatro conselhos municipais gestores de Itajaí/SC: Saúde, Assistência Social, Segurança Alimentar e Nutricional e do Idoso. Foram colhidas informações junto aos conselhos e aplicados 53 questionários aos participantes. A maioria está na idade adulta, são mulheres, possuem alto grau de escolaridade e foi indicada para o conselho sem eleição; metade recebe entre 1-5 salários mínimos e outra, entre 6-10 ou mais; um terço refere algum tipo de formação para atuar. O alto grau de escolaridade é recurso positivo, porém, pode indicar que as entidades valorizam apenas a participação de pessoas preparadas, excluindo as camadas menos favorecidas. Isto associado ao fato de que a maioria não foi eleita sugere que os representantes podem ser pouco legítimos e representativos. Os achados nos fazem considerar que existem alguns recursos positivos, porém outros nem tanto e há questões que devem ser aprofundadas para buscar maior compreensão em relação à possibilidade de influírem na participação. The creation of management councils from 1988 onwards led to various participative experiences, although authoritarian practices still prevail. However, there are possibilities for the involvement of civil society in public policies, provided separate groups explain and guarantee their rights, and exercise control over political decisions and the destiny of public resources. In the study presented here, the objective was to map resources for empowerment and participation, in four municipal management councils in Itajaí/SC: Health, Social Welfare, Food and Nutritional Safety, and the Elderly. The data was collected through documents and information gathered from the councils, and the application of 53 questionnaires to the representatives holding these positions. The majority of the participants were adults; women; with a high level of education; half of the participants earned from 1 and 5 minimum salaries and the other half, from 6 to 10 or more; most participants were nominated for the council without election; a third reported some kind of training for their positions; just over half were politically involved in the last municipal elections. The high level of formal education is a positive aspect in relation to the possibility of empowerment. However, this may indicate that the councils value only the participation of trained people and that the less privileged sectors of society are excluded. The results suggest that the representatives' identification with needs of the group is low. Although there are resources for participation, these is need to improve their understanding and use, for the empowerment of those involved.